Public good theory: a theoretical justification for permissive licence to use and re-use orphan works - Muhamad Khair, Muhamad Helmi; Mohamad Hashim, Haswira Nor; Anagnostopoulou, Maria (UUM Press, 2021)
This paper explored the adoption of Paul Samuelson’s Public Good Theory as a theoretical justification for a permissive licensing scheme that enables the use and re-use of orphan works in Malaysia. Orphan works are copyright-protected works with unloadable or unidentified right holders, and are currently on the rise due to the proliferation of unregistered, anonymous, and abandoned copyrighted works. The literature denotes the challenges arising from the difficulty faced by potential users in obtaining the permission for creative and innovative use of orphan works as required under the copyright law. Such challenges impede the potential use and re-use of orphan works for the purpose of knowledge dissemination, progress in the arts preservation, and digitization activities. This paper contributes to the current body of knowledge by canvassing two important issues. The first issue focused on the challenges faced by potential users to use and re-use orphan works in Malaysia. The second was Paul Samuelson’s Public Good Theory as a theoretical justification for permissive license to use and re-use orphan works. It is anticipated that a legislative reform grounded on Paul Samuelson’s Public Good Theory will spur grassroots innovations, creativity, and entrepreneurialism among members of the public. The permissive licensing scheme supports global calls for legislative reform of the copyright law to facilitate the use and re-use of orphan works.